PENGARUH DIGITAL MARKETING, MEDIA SOSIAL, DAN MARKETPLACE TERHADAP BRAND AWARENESS (Studi Kasus Pada Online Shop LittleLena) - Hulasoh Hulasoh; Bambang Mursito; Raisa A Hamidah (Jurnal AKTUAL, 2022)
This study aims to examine the effect of digital marketing, social media, and marketplace on Brand awareness (case study on online shop littlelena) The population used in this study is littlelena's followers with a sample of 100 respondents using a quantitative approach with the aim of testing the effect of digital marketing, social media, and marketplace on Brand awareness of the case study on the littlelena online shop. This research was conducted for 1 month, starting from August 1, 2021 to September 2, 2021. The results of this study indicate that the Digital Marketing variable does have a positive positive effect on the Brand awareness variable, the social media variable has a positive effect on the Brand awareness variable, and the Marketplace variable has a positive effect on Brand awareness, and there are positive effect and simultaneously between independent variabel on dependent variable.